Small G Proteins in Islet β-Cell Function - Kowluru, Anjaneyulu (The Endocrine Society, 2010)
Glucose-stimulated insulin secretion from the islet β-cell involves a sequence of metabolic events and an interplay between a wide range of signaling pathways leading to the generation of second messengers (e.g., cyclic nucleotides, adenine and guanine nucleotides, soluble lipid messengers) and mobilization of calcium ions. Consequent to the generation of necessary signals, the insulin-laden secretory granules are transported from distal sites to the plasma membrane for fusion and release of their cargo into the circulation. The secretory granule transport underlies precise changes in cytoskeletal architecture involving a well-coordinated cross-talk between various signaling proteins, including small molecular mass GTP-binding proteins (G proteins) and their respective effector proteins. The purpose of this article is to provide an overview of current understanding of the identity of small G proteins (e.g., Cdc42, Rac1, and ARF-6) and their corresponding regulatory factors (e.g., GDP/GTP-exchange factors, GDP-dissociation inhibitors) in the pancreatic β-cell. Plausible mechanisms underlying regulation of these signaling proteins by insulin secretagogues are also discussed. In addition to their positive modulatory roles, certain small G proteins also contribute to the metabolic dysfunction and demise of the islet β-cell seen in in vitro and in vivo models of impaired insulin secretion and diabetes. Emerging evidence also suggests significant insulin secretory abnormalities in small G protein knockout animals, further emphasizing vital roles for these proteins in normal health and function of the islet β-cell. Potential significance of these experimental observations from multiple laboratories and possible avenues for future research in this area of islet research are highlighted.